The Uniqueness of Strong Solutions for the Camassa-Holm Equation - Meng Wu; Chong Lai (Journal of Function Spaces and Applications)
Assume that there exists a strong solution of the Camassa-Holm equation and the initial value of the solution belongs to the Sobolev space H1(R). We provide a new proof of the uniqueness of the strong solution for the equation.